The Relationship between Tail Length and Elevation in Toque Macaques (Macaca sinica) in the Natural Habitat: usinga Quick Non-Invasive Method for Measuring Body to Tail Proportions - Huffman, M.A.; Kumara, R.; Nahallage, C.A.D.; Kawamoto, Y.; Jayaweera, P.M. (Proceedings of Asian Primate Symposium 2016, 2016)
Attached

The toque macaque o f Sri Lanka is classified into 3 sub-species; Macaca sinica sinica (dry zone), M. s. aurifrons (wet zone) and M. s. opisthomelas (hill zone), based on a combination o f phenotypical traits and climatic and ecological habitat distribution. We investigated the relationship between altitude and sub-species on relative tail length. Digital profile photographs were taken of 167 individual toque macaques from 27 localities distributed along elevationaf' (2~2129 masl) and climatic zones across the island. From these photos we created a pixelated proxy for tail length (base to tip) and body trunk length (base o f neck to base o f tail) o f each individual macaques using “Home o f LibreCAD, 2D-CAD” free ware (http://librecad.org/cms/home.html). From these measurements, we calculated a tail-to-trunk index (IT index) for the relative proportion o f tail to body length. A statistically significant relationship was found between T-T index and elevation (LMM 15.45, p < 0.0001). With every 100 m o f elevation increase, the TT index decreased by 0.031 (SE + 0.007). This morphological variation seems to be an adaptation to environmental conditions. This simple method is a promising new application for the non-invasive morphometric analysis o f species traits in the field.
Keywords: toque macaque; non-invasive methods; morphometrics; elevation; relative tail length; relative body trunk length